HBR's 10 must reads on entrepreneurship and startups - Sahlman, William Andrews; Hoffman, Reid; Andreessen, Marc; Blank, Steven G. (Steven Gary); Blank, Steven G. (Steven Gary). (Boston, Massachusetts : Harvard Business Review Press, 2018)
The best entrepreneurs balance brilliant business ideas with a rigorous commitment to serving their customers' needs. If you read nothing else on entrepreneurship, read these 10 articles by experts in the field. We've combed through hundreds of articles in the Harvard Business Review archive and selected the most important ones to help you build your company for enduring success. Leading experts and practitioners such as Clayton Christensen, Marc Andreessen, Steve Blank, and Reid Hoffman provide the insights and advice you need to: Build a business from the ground up Adopt lean startup practices like business model experimentation Be realistic about how prescient your business plan can truly be Focus on the most important part of your business: the people Connect powerfully with your audience of investors and customers - Understand where companies with the most impact are launching now--
Hiring an entrepreneurial leader / by Timothy Butler -- How to write a great business plan / by William A. Sahlman -- Why the lean start-up changes everything / by Steve Blank -- The president of SRI Ventures on bringing Siri to life / by Norman Winarsky -- In search of the next big thing: an interview with Marc Andreessen / by Adi Ignatius -- Myths about venture capitalists / by Diane Mulcahy -- Chobani's founder on growing a start-up without outside investors / by Hamdi Ulukaya -- Network effects aren't enough / by Andrei Hagiu and Simon Rothman -- Blitzscaling": an interview with Reid Hoffman / by Tim Sullivan -- Buying your way into entrepreneurship / by Richard S. Ruback and Royce Yudkoff -- The founder's dilemma / by Noam Wasserman.
"Featuring bonus article "Why the Lean Startup Changes Everything" by Steve Blank."
Print version record.
Master record variable field(s) change: 050, 082
Keywords: New business enterprises; Businesspeople; Entrepreneurship; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Businesspeople; Entrepreneurship; New business enterprises; elektronické knihy; electronic books